The 6th International Scientific Conference Creativity as a National Element: the Role of Individuality in the Framework of Creative Activities in the 21st Century - A. E. Ulanova (Концепт: философия, религия, культура, 2020)
From June, 30 to July, 2 2020 the 6th International Scientific Conference Creativity as a National Element: the Role of Individuality in the Framework of Creative Activities in the 21st Century took place in a novel on-line format. The event was organized by the Faculty of Humanities of the St. Petersburg State University of Economics in cooperation with the Department of Philosophy of MGIMO University, the Russian Philosophical Society and the Society of Russian Philosophy at the Ukrainian Philosophy Foundation. Researchers from Voronezh, Orel, Samara, Cheboksary, Chelyabinsk, Moscow and St. Petersburg, as well as from Serbia, Slovakia and Ukraine took part in the sessions. Those were: Psychological and Pedagogical Aspects of Creative Activity in Modern Educational Space, The Semantic Element of Artistic and Aesthetic Creativity, Metaphysical Foundations of the Creative Process. A range of papers and presentations were dedicated to various aspects of creativity in connection to modern issues of authority and society, information and transculturalism, legal consciousness and language, among which one should highlight those presented by MGIMO University scholars. Both the prognostic character of the topics in discussion and its format proved urgent and suitable amid the unfavorable epidemiological situation with its unpredicted effects.